DEVELOPMENT OF AN ETHNOSCIENCE DATABASE AND ITS IMPACTS ON STUDENTS LEARNING OUTCOMES IN BASIC SCIENCE IN SOUTHWESTERN NIGERIA (2014)
Scholars in the field of education identified prior cultural knowledge as a factor responsible for underachievement in science in countries where differences exist between learners' everyday life and the world of science. Previous studies focused on identification of cultural beliefs hindering achievements in science. However, they have not adequately addressed the use of this knowledge in improving learning. This study therefore developed an Ethnoscience database. The impact of the data on cognitive achievement in science, attitude to science and conception of scientific phenomena was also investigated. Moderating effects of school location and parent educational status were also determined. The database development involved gathering and sorting out common Yoruba expressions and identification of science-related ones. This is from the 232 expressions originally recorded from all the 3055 students of 12 secondary schools from peri-urban areas of three cities from three southwestern states and 31 elders and community leaders purposively selected from these areas. A pretest-posttest control quasi-experimental design with 2x2x3 factorial matrix was adopted for the field test with 352 Junior Secondary I students from two schools each in urban and rural areas of Ibadan. Instruments used were: Teachers Instructional Guide on Ethnoscience, Teachers Instructional Guide on Modified Lecture Method, Basic Science Cognitive Achievement Test (r=0.83), Attitude Towards Science Scale (r=0.86), Conception of Scientific Phenomena Assessment (r=0.82), Teachers Performance Evaluation Sheet and Ethnoscience Database. Three research questions were answered and seven null hypotheses tested at 0.05 level of significance. Data were analysed using descriptive statistics and Analysis of Covariance. One hundred and three common sayings expressing long-time observations and assertions, and some Yoruba beliefs and their related science concepts were identified. Ten of these expressions such as Lala to roke (belief in Ìwà) and Gravitational Force have similar interpretations, 17 such as Babatunde (belief in reincarnation) and Genetic Inheritance agree partially while 76 such as Abiku (belief in reincarnation) and Sickle cell Anaemia are contradictory. Significant main effects of treatment on cognitive achievement in science (F(1,339)=431.95; p<0.05), attitude to science (F(1,339)=39.78; p<0.05) and conception of scientific phenomena (F(1,339)=111.86; p<0.05) were recorded with Ethnoscience Instructional Method group performing better than the control group. There were no significant main effects of school location and parent educational status. Significant interaction effects of treatment and school location were recorded in both students' attitude to science (F(1,339) =3.28; p<0.05) and conception of scientific phenomena (F(1,339)=4.80; p<0.05) with school location influencing both in the Ethnoscience group. Effect size of treatment using Partial Eta-Squared ( ) was strong in cognitive achievement in science ( =0.56) but weak in attitude to science ( =0.11) and modest in conception of scientific phenomena ( =0.25). Yoruba expressions about Adi? n saba (longtime observations) agree with modern scientific concepts of Natural Incubation; Ara ?ango (belief in Ori?a) partially agree with Electrical discharge in Nitrogen Cycle and Ibinu Oluw?ri (belief in Ori?a) contradicts the concept of Trade-winds. Ethnoscience Instructional Method is effective in promoting cognitive achievement in science, attitude to science and conception of scientific phenomena. It is therefore recommended as an effective instructional method.